Diagnostic Yield of Image-Guided Percutaneous Core Needle Biopsy in Skeletal Lesions: A Retrospective Analysis - Maqsood, Mehreen; Shah, Azad Ahmad; Ali, Nadeem; Shiekh, Bilal Ahmad; Kawoosa, Altaf Ahmad (Annals of Pathology and Laboratory Medicine, 2025)
Background: Despite advances in radiology and imaging, histological diagnosis is of paramount importance in the management of musculoskeletal lesions. Traditionally, open biopsies are considered the gold standard but are associated with tumor cell contamination and a high complication rate. These issues can be addressed with a minimally invasive approach using a percutaneous core needle biopsy. In this study, we evaluated the diagnostic yield of core needle biopsy of bone lesions at our institute. Materials and Methods: This retrospective study of image-guided percutaneous core needle biopsy was conducted on 53 skeletal lesions, and the diagnostic yield of these biopsies was calculated based on the number of diagnostic and non-diagnostic core biopsies. Results: Among 53 skeletal lesion core needle biopsies, 39 had concordance with final open biopsy or the clinical outcome, making a diagnostic yield of 73.58%. Cystic skeletal lesion biopsies constituted 64.29% of the non-diagnostic core needle biopsies. When cystic lesions were excluded and only solid skeletal lesions were considered, the diagnostic yield improved to 87.80%. Conclusion: Percutaneous core needle biopsy of solid skeletal lesions is a cheap, less invasive, reliable, accurate, and cost-effective invasive procedure for histological diagnosis of skeletal lesions with the least complication rate. It should be considered as a first-line invasive diagnostic modality for the workup and management of skeletal lesions.